Arginine-glycine-aspartic acid-specific binding by foot-and-mouth disease viruses to the purified integrin alpha(v)beta3 in vitro. - Jackson, T; Sharma, A; Ghazaleh, R; Blakemore, W; Ellard, F; Simmons, D; Newman, J; Stuart, D; King, A (1997)
The integrin alpha(v)beta3 has been shown to act as the receptor for internalization of foot-and-mouth disease virus (FMDV) (A12), with attachment being through a highly conserved RGD motif located on the G-H loop of viral capsid protein VP1. In addition, however, we have recently shown that efficient infection of culture-grown cells by FMDV (O1BFS) requires binding to cell surface heparan sulfate. In this study, we have used a solid-phase receptor binding assay to characterize the binding by FMDV to purified alpha(v)beta3 in the absence of heparan sulfate and other cell surface components. In this assay, FMDV (O1BFS) successfully replicated authentic ligand binding by cellular alpha(v)beta3 in terms of its high affinity, dependence on divalent cations, and activation by manganese ions. Virus binding to this preparation of alpha(v)beta3 was exquisitely sensitive to competition by short RGD-containing peptides (50% inhibition at < 10(-8) M peptide), and this inhibition was highly sequence specific, with the equivalent RGE peptide being at least 10(4) fold less effective as a competitor. Representative viruses of the other six serotypes of FMDV bound to alpha(v)beta3 in a similar RGD-specific manner, although significant differences in sensitivity to RGD peptides suggest that the affinity of the different FMDV serotypes for alpha(v)beta3 is influenced, in part, by the variable amino acid residues in the VP1 G-H loop on either side of the RGD.